Fabrication and Characterization of Fe-Doped In2O3 Dilute Magnetic Semiconducting Nanowires - 张军然 吴振尧 刘玉杰 吕占朋 钮伟 王学锋 杜军 刘文卿 张荣 徐永兵 (中国物理快报：英文版, 2015)
Fe-doped In2O3 dilute magnetic semiconducting nanowires are fabricated on A u-deposited Si substrates by the chemical vapor deposition technique. It is confirmed by energy dispersive x-ray spectroscopy （EDS）, x-ray photoelectron spectroscopy （XPS） and Raman spectroscopy that Fe has been successfully doped into lattices of In2O3 nanowires. The EDS measurements reveal a large amount of oxygen vacancies existing in the Fe-doped In2O3 nanowires. The Fe dopant exists as a mixture of Fe2＋ and Fe3＋, as revealed by the XPS. The origin of room-temperature ferromagnetism in Fe-doped In2O3 nanowires is explained by the bound magnetic polaron model.